Perchlorination of Coronene Enhances its Propensity for Self‐Assembly on Graphene. Issue 3 (4th February 2016) - Conti, Simone; Rosso, Maria G. del; Ciesielski, Artur; Weippert, Jürgen; Böttcher, Artur; Shin, Yuyoung; Melinte, Georgian; Ersen, Ovidiu; Casiraghi, Cinzia; Feng, Xinliang; Müllen, Klaus; Kappes, Manfred M.; et al.
Abstract: The front cover artwork is provided by the Institut de Science et d'Ingénierie Supramoléculaires (ISIS, UMR 7006) at the University of Strasbourg. The image shows how perchlorofunctionalization of coronene enhances its propensity to form a self‐assembled monolayer at the liquid–graphene interface, as highlighted by the greater surface area covered by the perchlorocoronene. Read the full text of the Review at10.1002/cphc.201501113 Abstract : "We demonstrate that chemical functionalization of coronene by perchloro substitution significantly enhances its propensity to form a self‐assembled monolayer on graphene…" This and more about the story behind the front cover research can be found at10.1002/cphc.201600056 .